Family Visit to Albert and Rose Watkins in Huntington Beach - Watkins, Howard::::::::: (1983)
Rose Watkins feeding Gerber's baby food to Robin Watkins in portable car seat on kitchen table Robin wearing bib saying "I Love Grandma"